Associated factors for the occurrence of unintentional injuries in children from a low-income community in northeastern Brazil - doi 10.4025/actascihealthsci.v34i2.10313 - Vieira, Luiza Jane Eyre de Souza; Pordeus, Augediva Maria Jucá; Lira, Samira Valentim Gama; Moreira, Deborah Pedrosa; Pereira, Aline de Souza; Barbosa, Isabella Lima (Acta Scientiarum. Health Sciences, 2012)
Unintentional injuries reach high levels within the scope of morbidity and mortality worldwide, and have an impact on the quality of life of children and family members. This study depicts the socio-demographic profile of families in a community and identifies the factors associated with unintentional injuries in children. This is a cross-sectional study, developed with 362 families from a community in Fortaleza (Ceará State), by applying a questionnaire to the responsible adult in the family; the data were subjected to descriptive statistics by applying Pearson’s chi-square (x2) test, with p ≤ 0.05. From the results, 78% resided in the business area of the community, 71% survived with income up to the minimum wage, 62.7% were part of a nuclear family, and most residences showed risk factors for unintentional injuries. The data corroborate the literature by reaffirming the relationship between the socio-demographic and economic profile of families living in areas of socio-environmental vulnerability with the occurrence of unintentional injuries at home.